2004
DOI: 10.1039/b403905j
|View full text |Cite
|
Sign up to set email alerts
|

Control of molecular architecture by use of the appropriate ligand isomer: a mononuclear “corner-type” versus a tetranuclear [2 × 2] grid-type cobalt(iii) complex

Abstract: Employing two isomeric pyrazine-based ligands a [2 x 2] grid-type tetranuclear cobalt(III) complex, incorporating doubly deprotonated (La)2- ligands, and a "corner-type" mononuclear cobalt(III) complex, incorporating neutral H2Lp ligands in a zwitterionic form, have been synthesised and structurally characterised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…[1,2] Our research group has developed a range of ligands based around the diazines pyridazine, [3][4][5][6][7][8][9][10] pyrimidine [11][12][13] and pyrazine. [14][15][16][17][18][19][20] 4485 formed in MeOH. Five dimetallic (3Ј-6Ј and 9Ј) and one tetrametallic complex (15Ј) were structurally characterized: the ligands are bis-tetradentate and the metal centres are bridged through the pyrimidine ring.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Our research group has developed a range of ligands based around the diazines pyridazine, [3][4][5][6][7][8][9][10] pyrimidine [11][12][13] and pyrazine. [14][15][16][17][18][19][20] 4485 formed in MeOH. Five dimetallic (3Ј-6Ј and 9Ј) and one tetrametallic complex (15Ј) were structurally characterized: the ligands are bis-tetradentate and the metal centres are bridged through the pyrimidine ring.…”
Section: Introductionmentioning
confidence: 99%
“…70-80 % yield) of the desired SiF 6 2-compounds. The occurrence of SiF 6 2- ions in these compounds, rather than BF 4 -ions, was unexpected but was readily confirmed by the negative ion ESI mass spectrum, which showed a peak at m/z = 123.0 corresponding to the SiF 5 -anion, and the IR spectrum, which showed an intense broad split band (with peaks at 780 and 750 cm -1 ) typical of the SiF 6 2-ion. It has been reported that SiF 6 2-anions can arise in compounds originally containing BF 4 -ions as partial hydrolysis of the latter in the presence of moisture can generate traces of HF, which then react with the glassware to form SiF 6 2-ions.…”
Section: Pyrazine-25-dicarboxamide (H 2 L 1 ) and Nnј-bis[2-(2-pyrimentioning
confidence: 78%
“…Indeed, we have recently reported a cobalt(iii) [2 × 2] grid-type complex of the doubly deprotonated ligand (L 2 ) 2-. [5] Likewise, copper(ii) [6] and nickel(ii) [7] [8] These rather intractable solids have not been further characterised. In contrast, in the absence of added base, reactions Table 2, Table 3 and Table 4).…”
Section: Pyrazine-25-dicarboxamide (H 2 L 1 ) and Nnј-bis[2-(2-pyrimentioning
confidence: 99%
“…Brooker et al systematically studied on grid complexes of first transition metal ions that exhibit interesting structural, electrochemical and magnetic properties [31,32,[87][88][89][90]. The flat bisbidentate ligand dppn [3,6-bis(2-pyridiyl)pyridazine] has been used for preparation of copper(I) gridlike complexes in 1992 (Scheme 34) [91].…”
Section: Copper(i) Grid Complexesmentioning
confidence: 99%